The Impact of Glyphosate-Contaminated Soil on the Growth of Alfalfa - Cheng Bo; Tian Xiumin; Yue Zhengwen; Nan Ge; Wang Jian (E3S Web of Conferences)
Glyphosate is commonly used for weed control in agricultural fields, but improper use has led to significant residues of glyphosate in the soil. Excessive glyphosate can affect plant growth and the soil microenvironment. In this study, we planted alfalfa in soil sites previously treated with glyphosate and inoculated with rhizobia, observing crop growth and the structure of nitrogen-fixing microbial communities in the rhizosphere soil of the alfalfa. The results showed that: (1) Inoculating rhizobia promotes the growth of alfalfa; (2) compared to soil without a history of glyphosate use, soil with high concentrations of residual glyphosate resulted in a reduction of 10.1 cm (37%) in plant height, 5.5 g (46%) in fresh weight, and 1.9 g (47%) in root fresh weight in alfalfa plants, and high concentrations of residual glyphosate decreased the diversity of nitrogen-fixing microorganisms in the soil.